Protein nonadditive expression and solubility contribute to heterosis in Arabidopsis hybrids and allotetraploids - June, Viviana; Xu, Dongqing; Papoulas, Ophelia; Boutz, Daniel; Marcotte, Edward M.; Chen, Z. Jeffrey (Frontiers in Plant Science, 2023)
We analyzed fractionated proteomes to test protein abundance and solubility in Arabidopsis hybrids and polyploids. Many proteins in stress-responses are nonadditively expressed in intraspecific hybrids or allotetraploids. There are more soluble proteins of ribosomal biosynthesis and photosynthetic activities in the hybrids than in their parents but not in allotetraploids. In the allotetraploids, expression levels of protein homoeologs are biased for ~20% of nonadditively expressed proteins. Nonadditive protein expression and solubility may play a role in heterosis.